2011
DOI: 10.1007/s11302-011-9279-y
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptors expressed in human skeletal muscle fibres

Abstract: Purinergic receptors are present in most tissues and thought to be involved in various signalling pathways, including neural signalling, cell metabolism and local regulation of the microcirculation in skeletal muscles. The present study aims to determine the distribution and intracellular content of purinergic receptors in skeletal muscle fibres in patients with type 2 diabetes and agematched controls. Muscle biopsies from vastus lateralis were obtained from six type 2 diabetic patients and seven age-matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Notably, no additive effect of combining L-NA and indomethacin was detected, which is in agreement with NO mediating a part of the prostacyclin-induced vasodilation (33,48). We have previously shown by immunohistochemistry that P 2y 2 receptors are present on capillary endothelial cells (42), whereas other P 2y isoforms, including P 2y 11, appear to be present on skeletal muscle cells (5). The specific role of these receptors in the ATP-induced formation of NO and prostanoids remains to be resolved.…”
Section: Role Of No and Prostanoids In Interstitial Atp-induced Vasodsupporting
confidence: 80%
“…Notably, no additive effect of combining L-NA and indomethacin was detected, which is in agreement with NO mediating a part of the prostacyclin-induced vasodilation (33,48). We have previously shown by immunohistochemistry that P 2y 2 receptors are present on capillary endothelial cells (42), whereas other P 2y isoforms, including P 2y 11, appear to be present on skeletal muscle cells (5). The specific role of these receptors in the ATP-induced formation of NO and prostanoids remains to be resolved.…”
Section: Role Of No and Prostanoids In Interstitial Atp-induced Vasodsupporting
confidence: 80%
“…We investigated the skeletal muscle P2Y2 receptor content, since these receptors appear to be important mediators of ATP-induced vasodilation (34,39). We have previously shown that, in human skeletal muscle, P2Y2 receptors are present in microvascular endothelial and smooth muscle cells with no presence in skeletal muscle cells (4,24), suggesting that the change in skeletal muscle P2Y2 receptor content occurred in the vasculature. However, it is not possible to determine whether the increase in P2Y2 protein occurred specifically in endothelial and/or smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extracellular ATP stimulates translocation of GLUT4 to plasma membranes of muscle fibres [225]. Exercise increases interstitial concentrations of ATP [226], and a recent study showed immunohistochemical localisation of several P2 receptors on skeletal muscle plasma membrane, and on blood vessels, although the distribution was similar in samples from normal and T2D individuals [227]. …”
Section: Purinergic Signalling In Diabetesmentioning
confidence: 99%